Vai trò của tri thức lịch sử toán trong dạy học môn Toán ở trường phổ thông - Cao, Thị Hà; Đào, Phương Bắc; Đào, Thị Hoa Mai; Lê, Huy Hoàng (Tạp chí Giáo dục, 2025)
Mathematical knowledge is associated with specific historical and socio-cultural contexts. Mathematical knowledge may be the result of an individual’s great scientific effort or a product refined over multiple generations. Leveraging historical knowledge in mathematics teaching in secondary schools can help students gain insight into the scientific work, thinking methods, and problem-solving approaches of mathematicians, thereby enhancing student interest and cultivating their critical thinking skills. This paper highlights that historical mathematical knowledge helps students develop a positive attitude, stay motivated, and enhance their thinking skills in learning mathematics. The findings from this study will continue to be revised through experimental implementation to provide assessments and recommendations for mathematics teaching in secondary schools as well as for developing professional development program for mathematics teachers.